CHARACTERIZATION OF MELIPONICULTURE IN THE PROVINCE OF CIENFUEGOS, CUBA - Martínez Machado, José Andrés (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2023)
This research was carried out with the objective of characterize the hives, management system and health status of the stingless bee Melipona beecheii in the province of Cienfuegos. The survey was the method that used to evaluate all people with possession of colonies of M. beecheii bees Due to the lack of any registry that controls the meliponic activity in the province, the population and sample do not coincide. The 22 meliponicultores identified in the province do not carry out the activity in a professional manner, 90.9% manifest another work occupation. The average age is 42 years and the level of education reflects 22.72% in secondary school, 36.36% average technical, 22.72% finished pre-university and 18.18% are university students. The rational hives of Melipona beecheii showed good health, with a vital space per hive of maximum capacity and diferent models for the manufacture of their hives.